pengaruh iklim organisasi terhadap subjective well being perawat - Hairani Yainahu (Journal of Innovative and Creativity, 2025)
Subjective well-being, which includes aspects of life satisfaction, positive affect, and negative affect, is needed by nurses in carrying out their role in providing services to patients. This study aims to determine the effect of organizational climate on SWB. This study used a quantitative approach with 82 nurses as participants at X Hospital, Ternate. Data analysis was carried out using multiple linear regression with the help of SPSS version 25.00. The results showed that there was a significant influence between organizational climate and SWB, which means that the more positive the nurses' perceptions of organizational climate, the higher their SWB levels.